Kemampuan Matematika Permulaan Anak Usia 5-6 Tahun di TK Kecamatan Samarinda Ulu - Hasnur, Reyzia Anggriani; Maghfirah, Febry; Kartika, Wilda Isna (UNIB Press, 2025)
This study aims to describe the mathematical abilities of 5-6-year-old children in kindergartens across Samarinda Ulu Subdistrict. The 2018 and 2022 PISA results indicate that Indonesia's mathematical abilities are still below the global average (around 500) (L. Sulistyo & Dwidayati, 2021). This problem is also found in several kindergartens in Samarinda Ulu Subdistrict, with some teachers reporting difficulties in students' ability to sequence numbers 1 through 20. This study uses a quantitative approach with a survey research design. Data were collected through questionnaires given to kindergarten teachers who teach 5-6-year-old children (Group B) in Samarinda Ulu Subdistrict. The number of participants in this study was 100 children. Data analysis was performed using SPSS version 22.0. The results showed that the early mathematical abilities of 5-6-year-old children in Samarinda Ulu Subdistrict still need to be improved. The average score of children's abilities on the 22 items observed was 2.01, which indicates that children's abilities are still in the